KEBIJAKAN KEAMANAN AUSTRALIA TERHADAP ANCAMAN TIONGKOK DI PASIFIK SELATAN TAHUN 2017-2022 - Benedetta Claryssa; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research analyses Australia's security response to Chinese security threats in the South Pacific. China's presence in the South Pacific with economic assistance, military assistance, and security cooperation have raised concerns for Australia. This concern has made Australia, a regional power in the South Pacific, view China as a threat. Australia's concern is evidenced in Australia's 2020 Defence Strategic Update, which states that Australia is worried about the potential danger, especially in the military threat that China will pose due to expanding its influence in the Indo-Pacific. Australia is making efforts to respond to threats by balancing. This study uses a qualitative method with library research techniques, namely data collection through literature studies sourced from several books, journals, articles, state documents, and websites. This study uses the perspective of Neorealism and the theory of Balance of Threat. This theory explains that the state responds to threats by balancing. The results of this paper are in accordance with the Balance of Threat theory which indicates that Australia responded to China's threat in the South Pacific by carrying out a Pacific Step-up, a military alliance with the United States and Britain and conducting a quadrilateral security dialogue with the United States, Britain and India. Keywords: Chinese Influence, Australian Security, Strategic Defence, Balance of Threat.